1998
DOI: 10.1038/sj.jhh.1000646
|View full text |Cite
|
Sign up to set email alerts
|

A hypertensive father, but not hypertensive mother, determines blood pressure in normotensive male offspring through body mass index

Abstract: This investigation was to assess the role of genetic loading of hypertensive parents in the determination of blood pressure (BP) in their normotensive offspring. The medical check-up data from 7279 Japanese university students aged 19.22 ± 0.01 years were analysed of which 641 students had only one hypertensive parent with or without hypertensive grandparents, and from this number 609 cases were available for the present analysis. The BP in the students having only one hypertensive parent were in the normotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…We crossed SHR/crl with our WKY rats and failed to find an SHR Y chromosome blood pressure effect (9). Recent human studies further support our hypothesis and show that a hypertensive father but not a hypertensive mother affects blood pressure in normotensive male offspring through body mass index (10). Also, Lemne (11) showed that there was increased blood pressure reactivity in children of borderline hypertensive fathers.…”
Section: Y Chromosome Blood Pressure Effect In Other Laboratories -Ansupporting
confidence: 59%
“…We crossed SHR/crl with our WKY rats and failed to find an SHR Y chromosome blood pressure effect (9). Recent human studies further support our hypothesis and show that a hypertensive father but not a hypertensive mother affects blood pressure in normotensive male offspring through body mass index (10). Also, Lemne (11) showed that there was increased blood pressure reactivity in children of borderline hypertensive fathers.…”
Section: Y Chromosome Blood Pressure Effect In Other Laboratories -Ansupporting
confidence: 59%
“…10 Finally, studies in the sons of hypertensive parents suggest a possible role of the human Y chromosome in the determination of BP and body mass index in men. 44 Thus, the relevance of our current findings in the SHR-BN rat model for human hypertension and associated metabolic disturbances could be tested in association studies that use polymorphisms in candidate genes on the Y chromosome to screen human populations.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Moreover, human studies have shown that a hypertensive father but not a mother affects BP in normotensive male offspring. 9 Recently, Ellis et al 10 reported an association between an increased risk of elevated diastolic blood pressure (DBP) and a biallelic polymorphism on the NRY region of the Y chromosome in 409 subjects recruited from the general population in Victoria, Australia. However, it cannot be excluded that other polymorphic loci contained within the NRY region of the Y chromosome or other autosomal loci might interact with the HindIII(ϩ/Ϫ) variant to affect systolic BP (SBP) and DBP.…”
mentioning
confidence: 99%